How Firms Should Hedge - Brown, Gregory W.; Toft, Klaus Bjerre (Review of Financial Studies, 2002)
Substantial academic research explains why firms should hedge, but little work has addressed how firms should hedge. We assume that firms can experience costly states of nature and derive optimal hedging strategies using vanilla derivatives (e.g., forwards and options) and custom “exotic” derivative contracts for a value-maximizing firm facing both hedgable (price) and unhedgable (quantity) risks. Customized exotic derivatives are typically better than vanilla contracts when correlations between prices and quantities are large in magnitude and when quantity risks are substantially greater than price risks. Finally, we discuss how our model may be applied in practice.